Pendampingan Fisoterapi Infrared dan Pelatihan Perakitan Media Kabel UTP dan RJ45 Untuk Komunikasi Data pada Siswa - Erika Loniza Erika Loniza; Anna Nur Nazilah Chamim; Kurnia Chairunnisa (Ilin Institute, 2023)
The purpose of this community service activity is to educate and increase the understanding of class VII ICT students at SMP Muhammadiyah 7 Yogyakarta regarding pain and how to handle it and educate about computer network processes. The method used is by counseling and training. Counseling is carried out to increase education and understanding regarding the understanding of pain and computer network processes. While the training was conducted to train students to use medical therapy devices, namely infrared so that they can be used independently by them and training on making UTP cables with Rj45 connectors for LAN computer network data communications. There are two sessions in this activity, namely education and training on the use of infrared therapy devices as well as education and training for UTP and Rj45 cables. The activity was enthusiastically attended by students because this activity was something new for them marked by partners who hoped that there would be community service activities like this in the future. In addition, after the activity is carried out, mentoring will be held for 3 months so that the knowledge provided can be applied properly.